Religious cognitive behavioral therapy in specific phobia: a case report - Ridzwan, Hijaz; Sharip, Shalisah; Hanim, Afidatul (Malaysian Psychiatric Association, 2020)
This is a case report on the effectiveness of Religious Cognitive Behavioural Therapy sessions on a patient with Specific Phobia. The Word Health Organization (WHO) has included the spiritual aspect in its definition of health, with increasing attention being given to the role of religious beliefs and practices. We explore the role of RCBT which serves as an effective method of managing anxiety issues.